Bifunctional role of Pd/MMT-K 10 catalyst in direct transformation of furfural to 1,2-pentanediol - Date, Nandan S.; Chikate, Rajeev C.; Roh, Hyun-Seog; Rode, Chandrashekhar V. (Catalysis Today, 2018)
The acid functionality of montmorillonite clay K 10 (MMT-K 10) was found to play a key role to give 1,2-pentanediol (1,2-PeDO) in Pd catalysed furfural hydrogenation. Among various Pd loadings on MMT-K 10, 3% Pd/MMT-K 10 catalyst exhibited excellent performance giving almost complete conversion of FFR and the highest selectivity of 66% to 1,2-PeDO. Py-IR of the catalyst evidenced the presence of Brønsted acidity which was responsible in C5-O cleavage of furan ring after the formation of furfuryl alcohol which is the first step intermediate in FFR hydrogenation. At a lower temperature of 140 °C, highest selectivity of 56% was achieved for FAL while increase in temperature to 220 °C, enhanced the selectivity to 1,2-PeDO. Keeping the temperature constant at 220 °C, with increase in H2 pressure from 500 to 750 psig, resulted in decrease in 1,2-PeDO selectivity from 66 to 34% with proportionate increase in THFAL selectivity. Thus as per the requirement, the product selectivities can be tailored by varying the reaction parameters suitably. Several control experiments were also performed the results of which combined with the characterization data allowed to propose a plausible reaction pathway for the formation of 1,2-PeDO.

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Single-pot reductive rearrangement of furfural to cyclopentanone over silica-supported Pd catalysts - Date, Nandan S.; Kondawar, Sharda E.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ACS Omega, 2018)
Direct one-pot hydrogenation of furfural (FFR) to cyclopentanone (CPO) was investigated over different silica-supported Pd catalysts. Among these, 4% Pd on fumed silica (4%Pd/f-SiO2) showed remarkable results, achieving almost 98% furfural (FFR) conversion with similar to 89% selectivity and 87% yield to cyclopentanone at 165 degrees C and 500 psig H-2 pressure. More interestingly, the fumed-silica-supported catalyst tuned the selectivity toward the rearrangement product, i.e, cyclopentanone, whereas all of the other supports were found to give ring hydrogenation as well as side chain hydrogenation products due to their parent Bronsted acidity and specific support properties. X-ray diffraction data revealed the presence of different phases of the face-centered cubic lattice of metallic Pd along with lowest crystallite size of 15.6 nm in the case of the silica-supported Pd catalyst. However, Pd particle size was found to be in the range of 5-13 nm with even dispersion over the silica support, confirmed by high-resolution transmission electron microscopy analysis. While studying the effect of reaction parameters, it was observed that lower temperature gave low furfural conversion of 58% with only 51% CPO selectivity.. Similarly, higher H-2 pressure lowered CPO selectivity with subsequent increase in 2-methyl furan and ring hydrogenation product 2-methyl furan and 2-methyl tetrahydrofuran. Thus, as per the requirement, the product selectivity can be tuned by varying the type of support and/or the reaction parameters suitably. With the help of several control experiments and the characterization data, a plausible reaction pathway was proposed for the selective formation of cyclopentanone.

Preparation and activity of copper-gallium nanocomposite catalysts for carbon dioxide hydrogenation to methanol - Hengne, Amol M.; Yuan, Ding Jier; Date, Nandan S.; Saih, Youssef; Kamble, Sanjay P.; Rode, V. Chandrashekhar; Huang, Kuo-Wei (Industrial & Engineering Chemistry Research, 2019)
Copper (Cu) nanocomposite catalysts with gallium (Ga) and aluminum (Al) were prepared using the simultaneous coprecipitation digestion method. The catalysts were characterized by N-2 adsorption, N2O titration, XRD (X-ray diffraction), H-2-TPR (H-2 temperature-programmed reduction), XPS (X-ray photoelectron spectroscopy), and CO2-TPD (CO2 temperature-programmed desorption) techniques, and CO2 hydrogenation to methanol synthesis was performed. The use of Ga in Cu catalysts enhanced the weak basic sites more than the Cu catalysts with Al. With the CuGa nanocomposite formation, the catalyst showed a sequential reduction of CuO, for example, Cu+2 to Cu+ to Cu-0, and the Cu surface area was also high in comparison with CuAl. These findings confirmed that both the Cu surface area and CuO reducibility in the catalyst helped to boost the conversion of CO2, whereas selectivity to methanol was associated with the basicity of the catalyst. CuAl catalysts showed very poor selectivity to methanol despite CO formation, which could be due to the weak interaction of the CuAl nanocomposite catalysts compared to the CuGa nanocomposite catalysts.

One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism